2023
DOI: 10.1590/s1678-9946202365013
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON-TB Gold Plus and QuantiFERON-TB Gold In-tube assays for detecting latent tuberculosis infection in Thai healthcare workers

Abstract: Detecting latent tuberculosis infection (LTBI) is important, especially in high-risk populations including healthcare workers (HCWs). QuantiFERON-TB Gold Plus (QFT-Plus) is a new version of the interferon-gamma release assays (IGRAs) to replace the QuantiFERON-TB Gold In-tube (QFT-GIT). However, data on the use of QFT-Plus for LTBI detection in high TB-burden countries are limited. This study was conducted in a TB-endemic setting in Thailand. HCWs were enrolled in the study and underwent both tests during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has been reported that TST caused more false-positive results compared to QFT testing due to the influence of BCG vaccination or other mycobacterial infections [ 7 , 22 ]. Recent studies reported the prevalence of LTBI among Thai HCWs and medical students assessed by QFT-Plus at 14.71% and 6.3%, respectively [ 23 - 24 ]. These figures were lower than the prevalence estimate of 32.73% in Thai nursing professionals working in a tertiary-care center reported recently [ 25 ] and lower than those in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TST caused more false-positive results compared to QFT testing due to the influence of BCG vaccination or other mycobacterial infections [ 7 , 22 ]. Recent studies reported the prevalence of LTBI among Thai HCWs and medical students assessed by QFT-Plus at 14.71% and 6.3%, respectively [ 23 - 24 ]. These figures were lower than the prevalence estimate of 32.73% in Thai nursing professionals working in a tertiary-care center reported recently [ 25 ] and lower than those in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The Interferon-Gamma Release Assay (IGRA) has shown moderate compassion and high specificity in detecting LTBI. A use of QuantiFERON® TB Gold Plus (QFT-Plus) is appropriate for LTBI discovery in countries burdened with TB (Matucci et al, 2023;Rudeeaneksin et al, 2023). The global estimate is that one in four individuals have LTBI.…”
Section: Introductionmentioning
confidence: 99%